Students as Co-Creators in Shaping the Future of Higher Education - Nataša Z. Janković; Nevena M. Buđevac (University of Belgrade, Teacher Education Faculty, 2023)
Based on broad empirical research on multilingualism done by members of the Circle U. University Alliance, this paper presents a comparative analysis between the responses of 906 students from Serbia and 976 students from the other eight universities of the Alliance. By completing a comprehensive questionnaire, the students presented their experience, opinions, attitudes, motivation and obstacles related to gaining knowledge and skills in foreign languages. The focus of this paper is on students' needs related to learning foreign languages on the one hand, and their experience with it through formal education on the other. According to the survey results, despite students' needs, the practice of foreign language learning, especially at the university level, is not in line with the goal of the EU language policy and European Commission's recommendations that each citizen should learn at least two foreign languages. Additionally, as the survey shows, students from Serbia are at a disadvantage in comparison to their colleagues from the other universities due to the ever-growing disappearance of multilingualism from their academic circles. A particularly negative trend is visible in the status of languages for specific purposes at Serbian universities. One of the main conclusions of this research is that students' voices need to be heard and their needs taken into consideration when shaping the future of higher education.